A comparison of the long‐term consequences of vaginal delivery versus caesarean section on the prevalence, severity and bothersomeness of urinary incontinence subtypes: a national cohort study in primiparous women. Issue 12 (21st June 2013) - Gyhagen, M; Bullarbo, M; Nielsen, TF; Milsom, I
<x xml:space="preserve">Abstract</x> Objective To study the effect of one vaginal delivery (VD) compared with one caesarean section (CS) on the prevalence, severity and bothersomeness of urinary incontinence (UI) subtypes—stress (SUI), urge (UUI) and mixed (MUI)—20 years after delivery. Design Registry‐based national cohort study. Setting Women who returned postal questionnaires (response rate 65.2%) in 2008. Population Primiparae with one birth in 1985–88 (n = 5236) and no further births. Methods Medical Birth Register data were linked to a questionnaire. Analysis of variance and multivariate analysis were used to obtain adjusted prevalences and odds ratios (adjOR). Main outcome measures Prevalence, risk factors, severity, bothersomeness of UI subtypes. Results The prevalence of SUI, UUI and MUI was 15.3, 6.1, 14.4%, respectively, and was higher for all subtypes after VD versus CS. Moderate to severe incontinence was more prevalent after VD (21.3%) compared with CS (13.5%; adjOR 1.68, 95% confidence interval [95% CI] 1.40–2.03). Bothersome incontinence differed between MUI (38.9%), UUI (27.1%) and SUI (18.0%). The prevalence of bothersome UI was higher after VD compared with CS (11.2 versus 6.3%; adjOR 1.85, 95% CI 1.42–2.39) and consulting a doctor for UI was reported more often after VD than CS. Bothersome MUI occurred in 40.0% of incontinent women after VD compared with 29.9% after CS (adjOR 1.65, 95% CI 1.07–2.54). Symptomatic pelvic organ prolapse was an important modifier of UI with regard to its prevalence, duration, type and bothersomeness. Conclusion The prevalence of SUI, UUI and MUI was higher and moderate to severe UI and bothersome UI were reported more often after VD than CS 20 years after one delivery.